Non-communicable diseases and its risk factors among the transgender population in Kerala: a cross-sectional study - Bhavya Fernandez; Rakhal Gaitonde (BMC, 2024)
Abstract Background Non-communicable diseases (NCDs) are high on the priority list of the Kerala government, and exploring the extent to which transgender and gender diverse (TGD) community members benefit from the services of national programmes for NCDs can provide valuable insights on improving the inclusivity of the health system as it moves towards Universal Health Coverage. This study was conducted to explore the prevalence of NCD risk factors as well as facilitators and barriers to NCD management among the TGD population in Kerala. Methods A multiple methods study, including a cross-sectional survey of 120 self-identifying TGD people that included an adaptation of the WHO STEPS questionnaire, as well as in-depth interviews with thirteen individuals, was conducted in three districts of Kerala to explore the barriers and facilitators to NCD prevention and management. Results The results are presented using the key dimensions emerging out of the Diederichsen framework. A range of discrimination faced by TGD people in Kerala traps them in situations of low educational outcomes with consequent disadvantages in the job market when they search for livelihoods. This results in a large proportion of our sample living away from families (69 percent), and finding themselves in precarious jobs including sex work (only 33 percent had a regular job), with all these aforementioned factors converging to marginalise their social position. This social position leads to differential risk exposures such as increased exposure to modifiable risk factors like alcohol (40 percent were current alcohol users) and tobacco use (40.8 percent currently used tobacco) and ultimately metabolic risk factors too (30 and 18 percent were hypertensive and diabetic respectively). Due to their differential vulnerabilities such as the discrimination that TGD people are subjected to (41.7 percent had faced discrimination at a healthcare centre in the past one year), those with higher exposure to risk factors often find it hard to bring about behavioural modifications and are often not able to access the services they require. Conclusions The disadvantaged social position of TGD people and associated structural issues result in exacerbated biological risks, including those for NCDs. Ignoring these social determinants while designing health programmes is likely to lead to sub-optimal outcomes.